The perception on feminist movement among female students in UiTM Puncak Alam / Nur Afiqah Basar - Basar, Nur Afiqah (2019)
The word of feminist is increasingly being heard by society nowadays. Feminism is generally can be defined as a social and ideological movement that equalizes rights between women and men or commonly know more as gender equality in all fields, including education, politics, law, social and industry in the formal and informal sectors. Feminism voices out for justice and eliminates violence and gender discrimination. However, day to day, the feminist movement in Malaysia started to voice out their demands that clearly against Shariah rules and is shows the movement is mixed up with liberalism. Regarding that issues, the aim of this research is to review the young generation especially among female students about their perceptions and level of knowledge about feminist movement. In addition, this research also will identify the history and the influence of feminist movement in Malaysia. This study will be done by doing a quantitative method and collected data through an online survey or to achieve all the objectives. Result shows majority of the respondents are knowledgeable and against with the implementation of feminist movement in Malaysia.